Produção institucional na perspectiva arquivística: Memória e patrimônio documental - Viana, Gilberto Fladimar Rodrigues [UNESP]; De Carvalho Madio, Telma Campanha [UNESP] (My University, 2013)
An analysis is provided, from the archival perspective, of the research projects preserved in the database of the Universidade Federal de Santa Maria (UFSM), in the state of Rio Grande do Sul, developed from 1992 to 2012 in the area of arts and letters. We analyzed the evolution of the number of completed projects and their financial impact to the subunits of research and their effect on the academic career of the project coordinators. It was found that the database is of fundamental importance for both the university management and the academic leadership, and that, therefore, a dissemination and socialization policy of the institutional scientific production should be established, aiming at the society in general.
Production under the archival perspective: Memory and documentary heritage
Keywords: Archival perspective; Databases; Digital media; Documentary heritage; Institutional production